Promoting political engagement among youth : analysis of speech act patterns in Syed Saddiq's speech - Hadirah Amalin Hisham; Fuzirah Hashim (Penerbit Universiti Kebangsaan Malaysia, 2022)
It has been observed that speech act theory studies have mainly focused on Western orators and societies, whereas studies conducted on Eastern orators are still limited and insufficient, especially on youth speakers and youth political representatives in Malaysia. This paper will report on illocutionary type features of Speech Acts used in Syed Saddiq’s (a young member of Parliament for Muar) ‘A Lost in Generation: Youth in Politics’ speech and explain how the identified illocutionary type features project the messages in the speech. His speech has inspired the thoughts and beliefs of young minds through the power of his passionate words and a variety of language resources. The research used a descriptive qualitative research design and investigated the types of illocutionary acts based on the Taxonomy of Illocutionary Acts by John Searle (1975). The qualitative analysis of the data revealed that Syed Saddiq’s speech mainly employed representative and directive acts. Further analysis of the data also suggested that Syed Saddiq tended to implore the audience in his speech to persuade and motivate them to act and create a change in the political scene as Malaysian youths. The results of this study propose that political figures and speech writers may employ a specific speech act or illocutionary type to deliver a persuasive political speech to successfully persuade the target audience, i.e., youth or university students, to accept suggestions and opinions in order to break the cycle of political apathy and foster political interest in the younger generation.